A multiwavelength exploration of the [C II]/IR ratio in H-ATLAS/GAMA galaxies out to z = 0.2 - Ibar, E.; Lara-Lopez, M.A.; Herrera-Camus, R.; Hopwood, R.; Bauer, A.; Ivison, R.J.; Micha owski, M.J.; Dannerbauer, H.; van der Werf, P.; Riechers, D.; Bourne, N.; Baes, M.; et al. (Oxford University Press, 2015)
We explore the behaviour of [C ii] λ157.74 μm forbidden fine-structure line observed in a sample of 28 galaxies selected from ∼ 50 deg2 of the Herschel-Astrophysical Terahertz Large Area Survey survey. The sample is restricted to galaxies with flux densities higher than S160 μm > 150 mJy and optical spectra from the Galaxy and Mass Assembly survey at 0.02 < z < 0.2. Far-IR spectra centred on this redshifted line were taken with the Photodetector Array Camera and Spectrometer instrument on-board the Herschel Space Observatory. The galaxies span 10 < log(LIR/L⊙) < 12 (where LIR ≡ LIR[8-1000 μm]) and 7.3<log(L[CII]/L⊙)<9.3, covering a variety of optical galaxy morphologies. The sample exhibits the so-called [C ii] deficit at high-IR luminosities, i.e. L[CII]/LIR (hereafter [C ii]/IR) decreases at high LIR. We find significant differences between those galaxies presenting [C ii]/IR >2.5 × 10−3 with respect to those showing lower ratios. In particular, those with high ratios tend to have: (1) LIR <1011 L⊙; (2) cold dust temperatures, Td < 30 K; (3) disc-like morphologies in r-band images; (4) a Wide-field Infrared Survey Explorer colour 0.5 ≲ S12 μm/S22 μm ≲ 1.0; (5) low surface brightness ΣIR ≈ 108–9 L⊙ kpc−2, (6) and specific star formation rates of sSFR ≈0.05–3 Gyr−1. We suggest that the strength of the far-UV radiation fields (〈GO〉) is main parameter responsible for controlling the [C ii]/IR ratio. It is possible that relatively high 〈GO〉 creates a positively charged dust grain distribution, impeding an efficient photoelectric extraction of electrons from these grains to then collisionally excite carbon atoms. Within the brighter IR population, 11 < log(L IR/L⊙) < 12, the low [C ii]/IR ratio is unlikely to be modified by [C ii] self-absorption or controlled by the presence of a moderately luminous AGN (identified via the BPT diagram).